Effects of laccase and lactic acid bacteria on the fermentation quality, nutrient composition, enzymatic hydrolysis, and bacterial community of alfalfa silage - Bao, Xueyan; Feng, Haoran; Guo, Gang; Huo, Wenjie; Li, Qinghong; Xu, Qingfang; Liu, Qiang; Wang, Cong; Chen, Lei (Frontiers in Microbiology, 2022)
Ensiling has long been as a mainstream technology of preserving forage for ruminant production. This study investigated the effects of bioaugmented ensiling with laccase and Pediococcus pentosaceus on the fermentation quality, nutritive value, enzymatic hydrolysis, and bacterial community of alfalfa. The application of laccase and Pediococcus pentosaceus combination was more potent in modulating the fermentation quality of silage than laccase and Pediococcus pentosaceus alone, as indicated by higher lactic acid contents and lactic acid to acetic acid ratios, and lower pH, dry matter losses, and ammonia nitrogen contents. Moreover, treatments with additive enhanced protein preservation and structural carbohydrate degradation, while increasing true protein and water-soluble carbohydrate contents. By promoting lignin degradation, treatments containing laccase further facilitated the release of sugars from cellulose compared with treatment with Pediococcus pentosaceus alone. The additive treatments reduced the bacterial diversity and optimized the bacterial community composition of silage, with an increase in the relative abundance of desirable Lactobacillus and a decrease in the relative abundance of undesirable Enterobacter and Klebsiella. PICRUSt functional prediction based on Kyoto Encyclopedia of Genes and Genomes (KEGG) databases revealed that PL and LPL treatments increased the metabolism of membrane transport, carbohydrate, and terpenoids and polyketides related to fermentation activities. It can be concluded that bioaugmented ensiling with laccase and Pediococcus pentosaceus combination can be an effective and practical strategy to improve silage fermentation and nutrient preservation of alfalfa silage.